Advertising next 150 winning campaigns for the new communications age - Himpe, Tom. (San Francisco, Calif. Chronicle Books, 2008)
For decades, all advertising campaigns followed more or less the same pattern. However different the creative idea of message at the heart of them, campaigns were all expressed through the same mass channels and formats.

Today, campaigns have become complex and custom-made constructions, with different subcontractors involved from a range of specialist disciplines. Brands want their communication to be more like Frank Gehry building, remarkable and one-of-a-kind, and less like an ordinary house on the street, however attractive it might look on the inside.

As campaigns now tend to spread across a wide range of disciplines and channels, they have become increasingly complex and layered. Their construction requires the skills of an experienced architect, who is familiar with all the different building blocks and can make every aspect of the design fit together perfectly. It has become harder to summarize campaigns in a single catchphrase. They are more like riddles that have to be solved, or stories that have to be unravelled.

Contemporary campaigns are not easy to grasp or decode, nor do they want to be. They are living and breathing entities that make sense to those who fully engage to them, but whose essence can sometimes be hard to convey to outsiders.

Campaigns have also become more diverse. They can take many different shapes and forms, from one-off experience to a long-term service, from a series of webisodes to an online platform. Like Bam Stoker's Dracula, who could change shape in the right conditions, brands can adapt themselves to any environment, easily and comfortably, switching across disciplines and channels. The wide range of campaigns showcased in this book highlights the breadth of options available to marketers today.

The most fundamental evolution in today's communications landscape is the shift from short-term campaigns to long-term, structural initiatives. The advertising industry has always thought in terms of short-term spikes rather than ongoing dialogue.

So brands are increasingly attempting to build long-term, often self-sufficient platforms, whether it's an online community, a permanent service, or a physical space. All of the above initiatives have excelled at creating unique, permanent platforms that prevent the brand from simply making a string of sporadic appearances.
Includes indexes
Donated by Prof. Michelle Roxas
Keywords: Advertising